2018
DOI: 10.1186/s13640-018-0272-z
|View full text |Cite
|
Sign up to set email alerts
|

First-person reading activity recognition by deep learning with synthetically generated images

Abstract: We propose a vision-based method for recognizing first-person reading activity with deep learning. For the success of deep learning, it is well known that a large amount of training data plays a vital role. Unlike image classification, there are less publicly available datasets for reading activity recognition, and the collection of book images might cause copyright trouble. In this paper, we develop a synthetic approach for generating positive training images. Our approach synthesizes computer-generated image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, several authors used synthesized images to train deep learning model successfully [24][25][26][27][28]. This fact demonstrates that image synthetization is a technique that reduces the effort of manual annotations.…”
Section: Real or Virtual Imagesmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, several authors used synthesized images to train deep learning model successfully [24][25][26][27][28]. This fact demonstrates that image synthetization is a technique that reduces the effort of manual annotations.…”
Section: Real or Virtual Imagesmentioning
confidence: 90%
“…Castro et al [27] generated synthetic structural magnetic resonance images for learning schizophrenia. Segawa et al [28] recognized first-person reading activity by synthetizing computer-generated images and real background images.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancement in automatic reviewing using machine vision such as deep learning and convolutional neural networks (CNN) have allowed the processing of large data sets to identify various features in images (Nweke, Teh, Al-Garadi, & Alo, 2018). However, processing of large dataset of egocentric/first-person images are still at their early stage of development (Segawa, Kawamoto, & Okamoto, 2018). Castro et al (2015) showed the prediction of daily activities from egocentric images using CNN.…”
Section: Data Processingmentioning
confidence: 99%